Percursos: práticas dos diretores de escola da rede municipal de São Paulo - Sanches, Sandra Maria (2019)
The present study aimed to analyze the performance of two school principals regarding the performance of their functions and their formation needs with the intent of answering the question about how they articulate their knowledge in the daily life of the school or what knowledge is used to deal with the day-to-day issues in the school in the face of the flow of pedagogical and bureaucratic activities, of increasingly intense control and monitoring resulting from educational policy actions. The theoretical basis to guide the studies presented here were the following concepts: habitus and practical sense of Pierre Bourdieu; school administration based on the classic studies of Carneiro Leão and Querino Ribeiro; types of leadership of Max Weber; performativity and managerialism of Stephen Ball. The research, with an ethnographic perspective based on the studies of Rockwell, was developed in two schools of the municipal school system of São Paulo and confirmed the hypothesis that the school principal does not learn or does not incorporate a certain way of administering school in initial or continuing education, but rather in the personal experiences that the principal experiences, ways to organize the school and act based on models that the principal adjusts to the real situations. From this it follows that there are spaces, gaps, possibilities for singular action that escape the structure that conforms or tries to model this action. The data obtained also allowed to add that the foundations of the actions of the directors and their conducts are anchored less in scientific knowledge and more in the previous experiences that compose their habitus in diverse situations as teachers, whose incorporated, actualized and adjusted dispositions revealed structuring elements that oriented strategies and positioning